Stability and multiplicity of standing waves for the inhomogeneous NLS equation with a harmonic potential. (February 2019) - Luo, Xiao
Abstract: In this article, we study the stability and multiplicity of normalized standing waves for the inhomogeneous nonlinear Schrödinger equation with a harmonic potential arising in nonlinear optics.